PEMANFAATAN METODE GEOLISTRIK RESISTIVITAS KONFIGURASI SCHLUMBERGER DALAM PENDUGAAN LAPISAN AKUIFER UNTUK POTENSI AIRTANAH DI DESA CEMARA KECAMATAN SUBOH KABUPATEN SITUBONDO - Prasetyo Rubiantoro (UIN Sunan Kalijaga Yogyakarta, 2016)
Prolonged drought impacts very significant for some areas of Indonesia causes the limited availability of surface water. Increasing need for clean water is not commensurate with the available surface water supply. Cemara village, Suboh District of Situbondo is one example of a water crisis in the dry season. Only rely on spring water from the mountains to meet the water needs of citizens. To improve the supply source of clean water, some alternative activities had been done, one of which is to identify subsurface aquifer layer with resistivity geoelectric method utilizing Schlumberger configuration. The research activities include measurements and observations in the field, data processing, and data interpretation. The results of processing and interpretation of the data concluded that the rock layers in the study site is in the form of soil or rock composed of volcanic tuff, breccia, sandstone, and sand as aquifer layers. At each point geoelectric identified aquifer layer that is able to store and distribute groundwater well at different depths. As a recommendation to carry out drilling , geoelectric point 2 has more potential aquifer layers . Aquifer layer was detected at a depth of 60 meters and 135 meters .